ETNOZOOLOGI UNTUK RITUAL ADAT DAN MISTIS MASYARAKAT DAYAK MALI DI DESA ANGAN TEMBAWANG KECAMATAN JELIMPO KABUPATEN LANDAK - M Dirhamsyah; Ahmad Yani; Yuliana Yuliana (JURNAL HUTAN LESTARI, 2022)
Ethnozoology is a branch of ethnobiology, namely the relationship between humans and the use of animals in the surrounding environment and is a link between human culture and the animals in their environment. The Mali Dayak community in Angan Tembawang Village, Jelimpo District is one of the Dayak sub-tribes located in Landak Regency which has a characteristic that distinguishes it from other Dayak tribes, one of which is its language. The Malian Dayak people are also very closely related to nature, where their lives are very dependent on nature. The purpose of this study was to record the types of animals used for traditional and mystical rituals. This study uses a snowball sampling technique, which is a method for identifying, selecting and taking samples in a network or continuous chain of relationships. The number of people who became respondents as many as 10 people. The data presented in the form of qualitative descriptive. The results showed that there were 8 species from 8 families and 4 classes, namely mammals, aves, pisces and insects which were used for traditional and mystical rituals by the Mali Dayak community. The parts of animals that are used are flesh, blood, fur and the whole body. The parts that are used for mystical value are the voice and the whole body.Keywords: Dayak Mali, Ethnozoology, Traditional RitualsAbstrakEtnozoologi merupakan salah satu cabang ilmu etnobiologi, yaitu hubungan manusia dengan pemanfaatan satwa yang berada di lingkungan sekitarnya dan merupakan keterkaitan antara kebudayaan manusia dengan satwa-satwa di lingkungannya. Masyarakat Dayak Mali di Desa Angan Tembawang Kecamatan Jelimpo merupakan salah satu sub suku Dayak yang terletak di Kabupaten Landak yang memiliki ciri khas yang membedakan dengan suku Dayak lainnya salah satu bahasanya . Masyarakat Dayak Mali juga sangat erat hubungan nya dengan alam, dimana hidup mereka sangat tergantung pada alam. Tujuan penelitian ini mendata jenis-jenis satwa yang dimanfaatkan untuk ritual adat dan mistis. Penelitian ini menggunakan teknik snowball sampling yaitu suatu metode untuk mengidentifikasi, memilih dan mengambil sampel dalam suatu jaringan atau rantai hubungan yang terus menerus. Jumlah masyarakat yang dijadikan responden sebanyak 10 orang. Data yang disajikan dalam bentuk deskriptif kualitatif. Hasil penelitian terdapat 8 spesies dari 8 famili dan 4 kelas yaitu mamalia, aves, pisces dan insecta yang dimanfaatkan untuk ritual adat dan mistis oleh masyarakat Dayak Mali. Bagian satwa yang dimanfaatkan yaitu daging, darah, bulu dan seluruh badan. Bagian yang dimanfaatkan untuk nilai mistis adalah suara dan seluruh badan.Kata kunci: Dayak Mali, Etnozoologi, Ritual Adat